High‐Throughput Isolation of Cell Protrusions with Single‐Cell Precision for Profiling Subcellular Gene Expression. (1st July 2019) - Zhang, Pengchao; Han, Xin; Yao, Jun; Shao, Ning; Zhang, Kai; Zhou, Yufu; Zu, Youli; Wang, Bin; Qin, Lidong
Abstract: Invading cancer cells extend cell protrusions, which guide cancer‐cell migration and invasion, eventually leading to metastasis. The formation and activity of cell protrusions involve the localization of molecules and organelles at the cell front; however, it is challenging to precisely isolate these subcellular structures at the single‐cell level for molecular analysis. Here, we describe a newly developed microfluidic platform capable of high‐throughput isolation of cell protrusions at single‐cell precision for profiling subcellular gene expression. Using this microfluidic platform, we demonstrate the efficient generation of uniform cell‐protrusion arrays (more than 5000 cells with protrusions) for a series of cell types. We show precise isolation of cell protrusions with high purity at single‐cell precision for subsequent RNA‐Seq analysis, which was further validated by RT‐qPCR and RNA FISH. Our highly controlled protrusion isolation method opens a new avenue for the study of subcellular functional mechanisms and signaling pathways in metastasis. Abstract : Die präzise Isolierung von Zellausläufern auf der Einzelzellebene zur Profilierung subzellulärer Genexpressionsebenen kann durch eine neu entwickelte mikrofluidische Plattform umgesetzt werden. Ausläufer zahlreicher Zellen werden durch Laser‐Capture‐Mikrodissektion (LCM) isoliert und mittels RNA‐Sequenzierung analysiert. Dies hilft beim Verständnis von Ausläufer‐bezogener Signalisierung in verschiedenen physiologischen Prozessen wie z. B. Metastase.